Microsatellites markers to study genetic relationships among cowpea (Vigna unguiculata) genotypes - LAL, HIRA; RAI, NAGENDRA; RAI, KRISHNA KUMAR; TIWARI, SHAILESH KUMAR (The Indian Journal of Agricultural Sciences, 2016)
Genetic diversity and phylogenetic relationships among 48 cowpea [Vigna unguiculata (L.) Walp.] genotypes collected from different places in India were evaluated using simple sequence repeat molecular markers. A set of 40 primer combinations developed from cowpea genomic/expressed sequence tags and evaluated for their ability to detect polymorphisms among the various cowpea genotypes. Eleven primer combinations detected polymorphisms; sixteen primer combinations were monomorphic, with the remaining 13 primer sets failing to yield PCR amplification products. From one to 5 alleles were found among the informative primer combinations. The genetic diversity of the sample varied from 0.02 to 0.39 (mean = 0.205). The polymorphic information content ranged from 0.12 to 0.86 (mean = 0.49). The inter-cluster representatives of distant clusters (based on morphological and molecular markers) would be more useful for choosing the parents in cowpea breeding programmes.